2017
DOI: 10.21649/akemu.v23i2.1587
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Health Care Expenditure among Women in Rural Areas of Pakistan

Abstract: Background: With Pakistan failing to achieve Millennium Development Goals we have now entered into a new era of Sustainable Development Goals. Decreasing child mortality, improving maternal health and increasing the proportion of births by trained birth attendants, are the areas with unmet goals. As 29.5% of population of Pakistan is below the poverty line, expenditure on maternal health care services is of great importance as it determines the utilization of health care services to a large extent. Objective: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The positive correlation between OOPE and household expenditure is oblivious since OOPE acts as an independent health cost category, including medical and non-medical spending, which is in line with the existing evidence [72]. The number of pregnancies reported a negative association with OOPE; a study conducted in India revealed a similar association [36]. The probable reason could be better financial management during pregnancy with previous experience.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The positive correlation between OOPE and household expenditure is oblivious since OOPE acts as an independent health cost category, including medical and non-medical spending, which is in line with the existing evidence [72]. The number of pregnancies reported a negative association with OOPE; a study conducted in India revealed a similar association [36]. The probable reason could be better financial management during pregnancy with previous experience.…”
Section: Discussionsupporting
confidence: 77%
“…High OOPE is a barrier to affordability and accessibility creating inequities in maternal health [28,29]. Studies performed in low and middleincome countries (LMICs) such as India [35], Pakistan [36], Zambia [37], and Ghana [38] revealed that OOPE is a significant barrier to optimal maternal care.…”
Section: Introductionmentioning
confidence: 99%
“…The positive correlation between OOPE and household expenditure is oblivious since OOPE acts as an independent health cost category, including medical and non-medical spending, which is in line with the existing evidence (59). The number of pregnancies reported a negative association with OOPE; a study conducted in India revealed a similar association (25). The probable reason could be better nancial management during pregnancy with previous experience.…”
Section: Discussionmentioning
confidence: 83%
“…High OOPE is a barrier to affordability and accessibility creating inequities in maternal health (21,22). Studies performed in low and middle-income countries (LMICs) such as India (24), Pakistan (25), Zambia (26), and Ghana (27) revealed that OOPE is a signi cant barrier to optimal maternal care.…”
Section: Introductionmentioning
confidence: 99%
“…Further, there was a negative relationship between the number of previous pregnancies and the magnitude of the OOPE. It is due to the experience gained in previous pregnancies that may have led to better nancial management, as con rmed in the studies done in Sri Lanka (40) and India (31). Also, it could be assumed that the lower OOPE occurs for subsequent pregnancies due to less anxiety, concern, and lack of time to pay attention to health seeking.…”
Section: Discussionmentioning
confidence: 96%